(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This research is about an enhancing community legal awareness of land right disputes through the use of legal aid institutions. This is a qualitative research design which was done at Bolaangmongondow Regency, Kotamabagu North Sulawesi from March - June 2019. The instrument used in this research was the observation sheet and checklist sheet. The method of conducting the research was done through legal counselling activities carried out in Bolaangmongondow Regency, Kotamabagu North Sulawesi aim to increase community legal awareness in understanding disputes over land rights through the use of legal aid institutions to realize community legal awareness. The result of the research is that the implementation of the legal counselling activities had made the community understand the mandate of the law which requires regional heads to become regional judges, who initially did not understand. Through lecturing method, questions and answers, and giving examples, the objectives of this activity are achieved. Then it is concluded that the community legal awareness of land rights disputes in Bolaangmongondow Regency, Kotamabagu North Sulawesi through the use of legal aid institution has been well enhanced.